2018
DOI: 10.3390/s18051567
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Electrochemical Sensor Based on PyTS–CNTs for Simultaneous Determination of Cadmium and Lead Ions

Abstract: A simple and easy method was implemented for the contemporary detection of cadmium (Cd2+) and lead (Pb2+) ions using 1,3,6,8-pyrenetetrasulfonic acid sodium salt-functionalized carbon nanotubes nanocomposites (PyTS–CNTs). The morphology and composition of the obtained PyTS–CNTs were characterized using scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and X-ray photoelectron spectroscopy (XPS). The experimental results confirmed that the fabricated PyTS–CNTs exhibited good selectivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Moreover, it can be found that only the PEDOT:PSS functionalized microcantilevers had reaction signals with resistance change of −1.347 Ω on average, and the unmodified microcantilever had no reaction to lead ions relative to the deionized water. This response in resistance changes presents the microcantilever bending due to the change of induced surface stress resulting from the PEDOT:PSS oxidized by lead ions [ 31 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can be found that only the PEDOT:PSS functionalized microcantilevers had reaction signals with resistance change of −1.347 Ω on average, and the unmodified microcantilever had no reaction to lead ions relative to the deionized water. This response in resistance changes presents the microcantilever bending due to the change of induced surface stress resulting from the PEDOT:PSS oxidized by lead ions [ 31 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…15 Therefore, to improve the adsorption behavior, a modified working electrode is employed to increase the conductivity, stability, sensitivity and specific surface area. 16 For decades, mercury electrodes have been widely used as working electrodes in anodic stripping voltammetry (ASV) owing to their broad cathodic ranges, but they also form amalgams with some heavy metals. 17 Therefore, recently, various modified electrodes have been used to detect harmful metals such as Cd 2+ , Pb 2+ , Hg 2+ , Zn 2+ , and Cu 2+ present in different sources in the environment by measuring the ASV current based on conductive polymers such as poly(1,5-diaminonaphthalene)/multi-walled carbon nanotubes, 18 BiNP/MWCNT/Nafion/GCE, 19 poly(1,5-diaminonaphthalene)/graphene, 20 graphene/polyaniline/polystyrene, 21 and poly(1,2-diaminoanthraquinone) (PDAAQ).…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, some interesting nanomaterials such as metal oxides, metal nanoparticles [19][20][21], graphene and its derivatives [20,[22][23][24][25], carbon/carbon nanotubes [26][27][28][29] nanocomposites [30] and so on have been explored for the electrochemical detection of heavy metal ions. But these materials tend to feature low surface area and hence result in low sensitivity of the sensor.…”
Section: Introductionmentioning
confidence: 99%